Analisis Penggunaan Fasilitas masjid dalam Peningkatan Pembelajaran Pendidikan Agama Islam: Fasilitas Masjid Untuk Peningkatan Pembelajaran Pendidikan Agama Islam - Zaenal Abidin; Ilman Ilman; Ahmad Sopyan (STIT Sirojul Falah Bogor, 2023)
The background of the research is that mosques have educational functions such as the development of humanist values ​​and general welfare. Islamic religious education lessons in schools, have activities that can be done in mosques other than for prayer, as well as all kinds of efforts to prosper, and function properly. The formulation of the problem is how to use mosque facilities in improving the quality of PAI learning in Cihideung Ilir Village and how to describe and analyze the use of mosque facilities and how to improve the quality of PAI learning. This study uses a qualitative approach using the case study method. The results of the research are (1). Forms of using mosque facilities in improving the Quality of Islamic Education Learning in Cihideung Ilir Village through Dhuhur prayer activities in congregation, reading of hadith riyadus sholihin after congregational prayers, mentoring or halaqah, tadarus after praying and mosques are also used to discuss PAI learning materials assigned by the teacher students and to find solutions to these problems. (2). Shows that the existence of a mosque as an adequate medium for learning Islamic religious education is quite influential on improving the quality of Islamic religious education learning optimally. Keywords: Analysis of Mosque Facilities, Quality of Islamic Studies Learning.